Feedback from the European Bioanalysis Forum liquid microsampling consortium: capillary liquid microsampling and assessment of homogeneity of the resultant samples. (11th April 2019) - Cobb, Zoe; Rohde, Morten; Love, Iain; Boutet, Valerie; Schroeter, Katrin; Hawthorne, Glen; Dillen, Lieve; Barfield, Matthew; Kandira, Abdullah; Kranenborgh, Marion; White, Stephen; Timmerman, Philip
Following the completion of a detailed experimental protocol into the potential inhomogeneity of capillary liquid microsamples, which was performed at seven European Bioanalysis Forum member companies, the summary and conclusion on the data are reported here. It has been demonstrated that it is possible to generate homogeneous samples using these microsampling techniques; that the resultant microsamples can be accurate and precise and that capillary liquid microsampling data can be consistent with conventional larger volume plasma samples. However, the data contain some variability which is contributed to by the different range of experiences that each investigating site had with these techniques. Therefore, knowledge of the compounds, well-designed experiments and experience with these techniques are essential for the delivery of high quality data.